Safety And Efficacy Of Vaginal Misoprostol In Treatment Of First Trimester Miscarriage - Emarah , Mohamed S. A. (Advances in Social Sciences Research Journal, 2020)
Objective: This study was conducted to determine the outcome of medical treatment with vaginal misoprostol in missed miscarriage. Methods: A randomized controlled study was performed in Benha Teaching Hospital between April 2016 and June 2017. Eighty patients diagnosed with miscarriage before 13 weeks of gestation and wanted to try medical treatment were included. A detailed ultrasound scan was performed to confirm the diagnosis. Patients took 400 microgram (mcg) of misoprostol vaginal as an initial dose, and repeated the same dose 4-6 hours apart. Successful medical abortion was defined as spontaneous expulsion of gestational products (including gestational sac, embryo, fetus, and placenta). Ultrasonography at least 24 hours later from the initial dose to assess the uterine cavity if gestational products were not expelled, surgical evacuation was performed. Results: About two-thirds of patients (77.5%) had a successful outcome. The median interval time from pill to expulsion was 18 hours in the successful medical treatment group. Conclusion: Medical treatment with vaginal misoprostol should be a proper option for the first trimester miscarriage, especially for the patient who want to avoid surgical procedure. We can reduce the unnecessary sedation or surgical intervention in the patients with the first trimester miscarriage.